Gambaran Tingkat dan Sumber Stres Mahasiswa Profesi Rumpun Ilmu Kesehatan Universitas Padjadjaran - Daranindra, Kirana Candradita; Iskandarsyah, Aulia; Setyowibowo, Hari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
During their professional education and training, healthcare profession students face various academic demands that can trigger stress. This research aims to provide an overview of the level of stress, sources of stress, efforts to cope with stress, and factors hindering stress management among students in the Healthcare Professions study programs at Padjadjaran University. A total of 53 students participated by filling out the General Stress Symptoms questionnaire and demographic questionnaires related to their respective faculties. The research results show that the majority of Healthcare Proffessions students at Padjadjaran University experience high levels of stress (64.15%). The most common stressors for these students come from academic factors (77.8%). Most students have made efforts to cope with the stress they experience (94.4%). The most common strategy used by students to cope with stress is talking to loved ones (77.8%). The most significant factor hindering students in managing stress is the lack of time due to academic busyness (70.4%).